2020
DOI: 10.1016/j.jpainsymman.2020.04.022
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Sociocultural Influences on the COVID-19 Measures—Reflections From Singapore

Abstract: The coronavirus disease 2019 (COVID-19) pandemic presents unique challenges to Asian countries like Singapore with a predominantly Confucian culture. Palliative care providers play an important role in supporting their patients and family members in these difficult times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…The pandemic-derived from the coronavirus disease 2019 (hereafter, "COVID-19") and characterized by a severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infectionhas had global effects. Furthermore, it has impacted people's lives, physical and mental health, and economic situation (1)(2)(3). Studies indicated that individuals were willing to pay up to $290 for a COVID-19 vaccine, while 10 to 20% would refuse to pay for a vaccine altogether (4, 5).…”
Section: Introductionmentioning
confidence: 99%
“…The pandemic-derived from the coronavirus disease 2019 (hereafter, "COVID-19") and characterized by a severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infectionhas had global effects. Furthermore, it has impacted people's lives, physical and mental health, and economic situation (1)(2)(3). Studies indicated that individuals were willing to pay up to $290 for a COVID-19 vaccine, while 10 to 20% would refuse to pay for a vaccine altogether (4, 5).…”
Section: Introductionmentioning
confidence: 99%
“…Adherence could be encouraged through public health education on the dangers of COVID 19 [ 18 ], and use of behavior change messages to encourage preventive practices. Understanding the sociocultural practices relevant to different communities is key in order to rightfully implement the measures and encourage compliance [ 45 , 89 ] for example patient care norms, in cases of isolation and quarantine. Continuous surveillance and research on effectiveness of the mitigation strategy rolled out by the government is important in informing and evaluating policy.…”
Section: Resultsmentioning
confidence: 99%
“…This could be due to cultural differences as a study showed that Asians, who practice collectivism culture, showed significantly greater fear and greater acceptance toward fear-related advertising messages than Americans, who practice individualistic culture [ 20 ]. This may be relevant to the local context as Confucianism which is commonly practised in Singapore, promotes collective norms [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%